Exploring nurses' postturnover experiences in their new employment: A self-determination and job-fit perspective - Ester Ellen Trees Bolt; Kenneth Cafferkey; Keith Townsend; Margreet van der Cingel (BRQ Business Research Quarterly, 2025)
Nurses are known for having to work in a demanding work environment. As a result of this, nurses often quit their job, hoping to get better working conditions elsewhere. In this wave of change, how do nurses experience postturnover re-employment? Based on self-determination and person-job fit theory, this article aims to explore the postturnover experiences of nurses working in Dutch health care. 56 interviews were conducted where nurses reflected upon experiences at their former and current employment. Three main themes were identified: (1) improved levels of mental and physical well-being, (2) alignment of job skills and job needs to work environment, and (3) enhanced professional network. Our findings are congruent with self-determination theory and person-job fit theory and extend the knowledge base on individual postturnover implications, highlighting that turnover, although often seen as a negative phenomenon from the perspective of an organization, can benefit those who change employers.
Keywords: M100; 650; Turnover; nurses; well-being; self-determination; job-fit